The first record of Lysmata rauli Laubenheimer and Rhyne, 2010 (Decapoda: Caridea: Lysmatidae) from the tropical eastern Atlantic - Peter Wirtz; Carlos J. Moura; Filipe T. Nhanquê; Castro Barbosa; Ester Serrão (Nauplius)
Abstract Here we report the first record of the shrimp Lysmata rauli Laubenheimer and Rhyne, 2010 in the eastern Atlantic, from the intertidal at Kere Island, Bijagós archipelago, Guinea-Bissau.